Dapsone - mechanism of action, safety of use and the role in the treatment of bullous pemphigoid according to current recommendations - Magdalena Żychowska; Aleksandra Batycka-Baran; Jacek Szepietowski; Wojciech Baran (Termedia Publishing House, 2016)
Dapsone has been used in the treatment of bullous pemphigoid (BP) for over 50 years. According to the 2015 European Recommendations, the treatment of choice in BP are potent topical corticosteroids. In this article, we present data from the literature on the mechanism of action, efficacy and safety of dapsone in BP. After an extensive search of the PubMed database, we identified one systemic review and 7 nonrandomized clinical trials assessing the efficacy of dapson in BP. Data from the literature indicate that monotherapy with dapsone may be effective in 20-45.4% of BP cases. Combined treatment with dapsone and topical potent corticosteroids increases the efficacy up to 63-76%. The combination of oral corticosteroids and dapsone induces remission in 92-100% of cases. According to many authors, dapsone may be an effective and safe corticosteroid-sparing drug. Still there is a need for randomized controlled trials assessing the effectiveness of different treatment options in BP cases.